Analisis Implementasi Pemberian Reward melalui Metode Token Ekonomi dalam Membentuk Kedisiplinan Anak Usia Dini 4-5 Tahun di Ra Al-Ghazali - Cut Nurul Haniyah; Zulfahmi Lubis; Hilda Zahra Lubis (STIKes Ibnu Sina Ajibarang, 2025)
This study was conducted at RA Al-Ghazali, which implements the use of an economic token system as a form of reward to foster discipline among children aged 4–5 years. The objectives of this study are to identify the level of discipline exhibited by children aged 4–5 years at RA Al-Ghazali, to describe the implementation of reward-giving through the economic token method in shaping discipline, and to describe the outcomes achieved after the application of this reward system. The study employed a descriptive qualitative method, focusing on direct observation, documentation, and descriptive analysis of children’s behavior during daily classroom activities. The results indicate that the economic token reward system positively impacts children’s discipline. Over a two-week implementation period, a noticeable improvement in discipline was observed. In the second week, out of 13 participating children, nine showed an increase in disciplined behavior, as reflected by the number of star tokens collected. The remaining four children did not demonstrate significant improvement due to their absence for several days in the second week, which limited their opportunity to collect tokens. Despite this, the findings suggest that the token economy method effectively motivates children to display disciplined behavior. Based on these results, it can be concluded that the application of the token economy is effective in fostering discipline among children aged 4–5 years at RA Al-Ghazali. Reward-giving through this method encourages children to comply with rules, take responsibility for tasks, and actively participate in learning activities. The study also highlights that the success of this method depends on the consistent attendance of children and the regularity of the token reward application, making proper management and monitoring essential for achieving optimal results. Therefore.